2019
DOI: 10.1073/pnas.1812171116
|View full text |Cite
|
Sign up to set email alerts
|

Differentially synchronized spiking enables multiplexed neural coding

Abstract: Multiplexing refers to the simultaneous encoding of two or more signals. Neurons have been shown to multiplex, but different stimuli require different multiplexing strategies. Whereas the frequency and amplitude of periodic stimuli can be encoded by the timing and rate of the same spikes, natural scenes, which comprise areas over which intensity varies gradually and sparse edges where intensity changes abruptly, require a different multiplexing strategy. Recording in vivo from neurons in primary somatosensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 51 publications
(71 reference statements)
1
58
0
Order By: Relevance
“…Therefore, NMDA inputs may mediate the discrimination of objects based on their macro-geometric featuresfor example, discriminating between your house key and car key when searching in your pocket. The differentiation between AMPA and NMDA input streams could be established for example via compartmentalized synaptic locations on the postsynaptic neuron dendrites [16] or by multiplexed neural coding [17]. Our models also suggest a tendency for sparseness and the involvement of a small set of key synaptic inputs from first-order neurons, supporting previous empirical work [18] and suggesting that imposing a sparseness constraint on the synaptic weights may improve discrimination performance [19].…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, NMDA inputs may mediate the discrimination of objects based on their macro-geometric featuresfor example, discriminating between your house key and car key when searching in your pocket. The differentiation between AMPA and NMDA input streams could be established for example via compartmentalized synaptic locations on the postsynaptic neuron dendrites [16] or by multiplexed neural coding [17]. Our models also suggest a tendency for sparseness and the involvement of a small set of key synaptic inputs from first-order neurons, supporting previous empirical work [18] and suggesting that imposing a sparseness constraint on the synaptic weights may improve discrimination performance [19].…”
Section: Discussionsupporting
confidence: 80%
“…The intensity, size and location of a stimulus can be conveyed rapidly by this neural code. Relative arrival times of the first action potentials might also contribute to the code, as observed in the visual system (Gollisch & Meister, 2008), and subsequent action potentials could enable multiplexing (Lankarany et al, 2019). We use a broad-class nociceptor line and it is possible that its subpopulations exploit a diversity of coding strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the presence of both coding strategies, whose feasibility was demonstrated in different neural systems (e.g., [ 16 , 17 ]), can be considered as a unique way to convey multiple features of the stimulus, i.e., multiplexed coding. In fact, in addition to the rate code, which is largely observed in different neural systems, inter-neuronal correlations within many areas of the brain have a significant functional role in the neural code [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is challenging to uncover the distinct roles of differentially correlated spikes—i.e., asynchronous spikes (rate code) and synchronous spikes (temporal code)—in a multiplexed code. To address this challenge, it is crucial to measure the information underlying different types of spikes [ 16 ]. Various information-theoretic techniques have been exploited to measure information carried by differentially correlated spikes [ 15 , 21 ].…”
Section: Introductionmentioning
confidence: 99%